Injury and Injury Prevention in United States Para Swimming: A Mixed-Methods Approach - Jay Salerno; Stephanie Tow; Elizabeth Regan; Stephen Bendziewicz; Matthew McMillan; Shana Harrington (North American Sports Medicine Institute, 2022)
# Background Para swimming has experienced increased participation in recent years. Injury and injury prevention research on Para swimmers is lacking compared to swimmers without impairment. # Purpose This study aimed to gather data in Para swimmers on typical injuries, injury prevention programs, and attitudes toward injury and injury prevention in this population. # Study Design Cross-sectional, mixed-methods design evaluating injuries, injury management, and injury prevention in elite Para swimmers in United States (U.S.). # Methods Para swimmers on the U.S. Paralympics Swimming National teams at multiple competition levels were invited to complete an online survey. Qualitative interviews with six U.S. Paralympics National team Para swimmers were conducted to provide detail on athlete experiences with injury and prevention. # Results Twenty-one of 56 surveys were returned: 11 of 21 participants (52.4%) reported experiencing an injury that altered their weekly training. All (21/21) reported participating in strength training and 19 of 21 (90.5%) reported incorporating stretching into their training regimen, although strengthening/stretching regimens included routines that may not have been specifically targeted toward injury prevention. Six of 21 (28.6%) reported participation in an injury prevention program. Qualitative interview themes included the impact of swimmers' compensated body mechanics on injury risk, the value of individualized injury prevention programs, and the importance of knowledgeable coaching and rehabilitation staff. # Conclusions Injury prevention programs are important components in Para swimming training although they are underutilized based on responses in this study. These programs should be individualized to address swimming biomechanics and athlete-specific impairments. Increasing coaching knowledge and access to individualized programs may reduce injury prevalence among this at-risk population. # Level of Evidence 3